2013
DOI: 10.1242/jeb.085548
|View full text |Cite
|
Sign up to set email alerts
|

Auto- and heterotrophic responses of the coralPorites luteato large amplitude internal waves

Abstract: SUMMARYLarge amplitude internal waves (LAIW) cause frequent and severe changes in the physico-chemical environment of Andaman Sea coral reefs and are a potentially important source of disturbance for corals. To explore the coral response to LAIW, prey capture disposition and photosynthesis were investigated in relation to changes in seawater temperature, pH, flow speed and food availability in LAIW simulation studies under controlled laboratory conditions, using Porites lutea as a model organism. Although food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
(89 reference statements)
0
19
0
Order By: Relevance
“…In contrast, another study observed that polyps from the coral P. lutea extended further under high CO 2 conditions24. During the second expedition, however, G. fascicularis polyps were expanded more, which happened to occur during a new moon compared to the first expedition that had a full moon.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, another study observed that polyps from the coral P. lutea extended further under high CO 2 conditions24. During the second expedition, however, G. fascicularis polyps were expanded more, which happened to occur during a new moon compared to the first expedition that had a full moon.…”
Section: Discussionmentioning
confidence: 87%
“…greater pH homeostasis at the site of calcification (Tambutté et al 2011(Tambutté et al , 2015. P. lutea has also previously been documented to acclimate to high environmental variance in temperature and pH through adjustments of heterotrophy versus photosynthetic nutrition (Pacherres et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…This is in line with previous studies showing different sensitivities of phytoplankton or corals to UVR and temperature (Halac et al ). In T. reniformis , thermal stress alone decreased zooplankton grazing rates, most likely due to polyp retraction (L. C., personal observation), which is known to depend on environmental factors such as light, flow, and temperature (Pacherres et al ). However, this significant reduction in heterotrophic nutrient acquisition (CHAR dropped from 96% to 34%) did not affect the short‐term calcification and photosynthesis of T. reniformis , which remained equivalent to control condition.…”
Section: Discussionmentioning
confidence: 99%